PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, BUDAYA ORGANISASI, KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL (Survei pada Karyawan PDAM Kota Surakarta) - Neneng Rahma, Suharno & Bambang Widarno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
The purpose of this study to analyze the effect of budget participation,organizational culture, leadership and organizational commitment on managerialperformance partially and simultaneously. This study is a survey. The studypopulation is an employee who has authority in the budgeting process in PDAMSurakarta as many as 47 employees and all of them are used as samples by usedcensus. type data used quantitative and qualitative data. The data source usedprimary data and secondary data. Methods of data collection used questionnairesand literature study data were analyzed used multiple linear regression.Participation budgetary, organization culture, leadership and organizationalcommitment has positive and significant effect on managerial performance partiallyand simultaneously.Keywords: participation budgeting, organizational culture, leadership,organizational commitment, managerial performance simultaneously.